RSD by UNHCR: difficulties and dilemmas - Abdelaaty, L (Refugee Studies Centre, University of Oxford, 2020)
The arrangements established between governments and UNHCR in relation to conducting RSD reflect the varying motivations of, and challenges for, both parties.